Personal Branding Pejabat Publik (Studi Kualitatif Personal Branding Bupati Tapanuli Selatan Melalui Akun Instagram @ Hajidollypasaribu) - Mhd. Latip kahpi (Hikmah, 2021)
AbstractBased on the results of research conducted regarding how the South Tapanuli Regent Dolly Parlindungan Pasaribu did personal branding through her Instagram account from September to November 2021, the following conclusions can be drawn based on observations made by researchers on content posted on the @hajidollypasaribu account. This research was conducted with a content analysis approach to see how personal branding was carried out by the South Tapanuli regent through the @hajidollypasaribu account. This approach will look at the content related to the content posted by Dolly Pasaribu. According to Harold D. Laswel Content Analysis is used to see how the content is expressed in the contents of the mass media, both printed and electronic. The Regent of South Tapanuli did personal branding on his Instagram account by using hashtags, geotags, mentions, likes, and comments. Posts made by the @hajidollypasaribu account generally since being sworn in as the regent of south tapanuli on February 26, 2020, have created a lot of content by taking advantage of the features owned by Instagram. The formation of personal branding carried out by the Regent of South Tapanuli by guiding the Specialization (The law of specialization), Leadership (The law of leadership), Personality (The law of personality), Visible (The law of visibility), Unity (The law of unity ), Firmness (The law of persistence), Good name (The law of goodwill). Of the several personal branding models carried out by the South Tapanuli Regent based on observations made by researchers, the most dominant is the personality (The law of personality) who is humble as it is without any settings. Then Firmness (The law of persistence), Good name (The law of goodwill).Keywords: Personal Branding, Public Official, Instagram AbstrakBerdasarkan hasil penelitian yang dilakukan terkait bagaimana Bupati Tapanuli Selatan Dolly Parlindungan Pasaribu melakukan personal branding melalui akun isntagramnya sejak september sampai november 2021 maka bisa ditarik kesimpulannya sebagai berikut berdasarkan hasil pengamatan yang dilakukan peneliti kepada konten yang diposting pada akun @hajidollypasaribu. Penelitian ini dilakukan dengan pendekatan analisis isi (conten analysis) untuk melihat bagaia personal branding yang dilakukan oleh bupati tapanuli selatan melalui akun @hajidollypasaribu. Pendekatan ini akan melihat isi terkait conten yang diposting oleh Dolly Pasaribu. Menurut Harold D. Laswel Analisa Isi ini digunakan untuk melihat bagaimana isi yang diuangkapan dalam isi media massa baik cetak maupun elektronik. Bupati tapanuli selatan melakukan personal branding di akun instgramnya dengan mememanfaatkan hastag, geotag, mention, like, dan comen. Postingan yang dibuat oleh akaun @hajidollypasaribu umumny sejak dilantik sebagai bupati tapanuli selatan 26 Februari 2020  banyak membuat conten dengan memanfaatkan fitur-fitur yang dimiliki oleh instagram. Pembentukan personal branding yang dilakukan oleh Bupati Tapanuli Selatan dengan mempedomani Spesialisasi (The law of specialization), Kepemimpinan (The law of leadership), Kepribadian (The law of of personality), Terlihat (The law of visibility), Kesatuan (The law of unity), Keteguhan (The law of persistence), Nama baik (The law of goodwill). Dari beberapa model personal branding yang dilakukan Bupati Tapanuli Selatan berdasarkan pengamatan yang dilakukan oleh peneliti, yang paling dominan adalah Kepribadian (The law of of personality) kepribadian yang humbel apa adanya tanpa settingan. Kemudian Keteguhan (The law of persistence), Nama baik (The law of goodwill).Kata Kunci: Personal Branding, Pejabat Publik, Instagram